Penance and Anointing of the Sick as Sacraments of Reconciliation and Healing: Use and Abuses Today - Anagwo, Emmanuel Chinedu (Cultural and religious studies, 2016)
This paper entitled, "Penance and Anointing of the Sick as Sacraments of Reconciliation and Healing: Use and Abuses Today" analyses the sacraments as means of renewal and commitment that can be useful in the project of New Evangelization. The important factor is the effective and efficacious use of the sacraments, assessed by how well they meet the basic needs of the faithful to know and worship God. Using theological, expository and analytical methods, the essay discusses the use and abuses that can promote reconciliation and healing, and conversely hinder them. Earlier, the paper briefly commented on the nature of Penance and Anointing of the Sick from a theological point of view. It argues that sacraments of Penance and Anointing of the Sick bestow sanctifying power, transform and renew the faithful who would participate in them well. With abuses the sanctifying grace is relegated to the background. However, it presented a few random thoughts on the liturgical implications, in order to provide a roadmap for renewal and commitment today. Both the ministers and recipients of the sacraments must be in a good state of mind and body towards the celebrations to have its full effects.